Relationship of Anti-Mullerian Hormone in Polycystic Ovary Syndrome Patients with Different Subgroups - Sumaiya Farooq, Sanobar Baloch, Shazia Awan, Fakharunissa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association between hyperandrogenism (HA) and polycystic ovarian morphology in a Chinese cohort of patients with polycystic ovary syndrome and the usefulness of anti-Mullerian hormone Methods: Patients who visited the Department of Obstetrics and Gynecology at Indus Medical College Tando Muhammad Khan between May 2020 and October 2020 were the subjects of a prospective case-control study. According to Rotterdam criteria, 50 females with Polycystic ovary syndrome (PCOS) and 50 females without the condition participated in the study. Results: An teenage patient clinic at our hospital enrolled 100 consecutive patients (50 by PCOS, 50 by healthy controls aged equal to the adolescent patients). Menstrual anomaly and hirsutism were most common in the study group, while vaginal discharge was most common in the control group. Analyses of anthropometric measures between the two groups showed a significant difference (p<0.05). In the PCOS group, both plasma fasting insulin (p-value = 0.001) and HOMA index (p value =0.003) had statistically greater values. PCOS patients also had significantly higher means of fT and 17-OH-P, as well as LH and LH/FSH ratios. Serum AMH levels were found to be negatively correlated with FSH levels in all patients (r=-0.238, p=0.031). The AUC value indicated by ROC analysis for distinguishing PCOS was 0.678. However, the sensitivity and specificity scores according to the highest Youden index were 47.8% and 76.1%, respectively. Conclusion: The Anti-Mullerian hormone level is also linked to the existence of polycystic ovary morphology, which suggests that the AMH level might have a role in the diagnosis and treatment of PCOS.